UNGKAPAN MAKNA MAKIAN DALAM BAHASA MINANGKABAU DAN BATAK: STUDI KOMPERATIF - usmala dewi siregar (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: Invective expression is different from its literal meaning. Invective expression reflect the speaker`s culture, customs, and social and historical backgrounds. Therefore, without knowing a target language, culture aspects as well as expressions, the meaning of expressions can not be concluded from the dictionary definition, speakers of foreign culture often face problems in understanding the actual meaning of the meaning of expressions, especially invective expressions. In the Minangkabau culture that uses invective expressions in their daily conversations, understanding that is not a problem. However, problems may occur when the two different cultures try to understand each other's expressions. Therefore, this study analyzed invective expressions in Minangkabau and Batak languages. In addition, the writer also examined aspects of the culture and situation of the intended expressions used by speakers of each language. The researcher used qualitative methods and the data gets from the informants of both cultures. These findings reveal two categories, namely, first, invective expression in Minangkabau and Batak languages with same literal and actual meaning. Second, invective expression in Minangkabau and Batak languages with same literal meaning but different actual meaning.Abstrak: Makna kiasan berbeda dengan arti harfiahnya. Makna kiasan mencerminkan budaya, adat istiadat penutur, dan latar belakang sosial dan historis. Oleh karena itu, tanpa mengetahui aspek budaya target dan juga ungkapan, makna ungkapan tidak dapat di simpulkan dari definisi kamus, penutur bahasa asing sering menghadapi masalah dalam memahami arti sebenarnya dari makna ungkapan khususnya ungkapan makian. Dalam budaya Minang yang menggunakan ungkapan makian dalam percakapan sehari-hari mereka, memahami itu bukanlah masalah. Namun, masalah mungkin terjadi ketika kedua budaya yang berbeda mencoba memahami ungkapan satu sama lain. Oleh karena itu, penelitian ini menganalisis ungkapan makian dalam bahasa Minang dan Batak. Selain itu peneliti juga meneliti aspek budaya dan situasi tujuan ungkapan di gunakan oleh penutur bahasa masing-masing. Peneliti menggunakan metode kualitatif dan Data bersumber dari informan kedua budaya. Temuan ini mengungkapkan dua kategori yaitu, pertama, Ungkapan makian dalam bahasa Minang dan Batak dengan makna literal dan makna aktual yang sama. Kedua, Ungkapan makian dalam bahasa Minang dan Batak dengan makna literal yang sama tapi makna aktual berbeda.